Biodiesel from Dodonaea Plant Oil: Synthesis and Characterization—A Promising Nonedible Oil Source for Bioenergy Industry - Bukhari, Syeda Alia Zehra; Ullah, Kifayat; Ahmad, Mushtaq; Zafar, Muhammad; Ullah, Anwar; Sultana, Shazia; Ibrahim, Mohamed Mousa; Hessien, Mahmoud Mohamed; Mersal, Gaber Ahmad Mahmoud; Ghoneim, Sherif Salama Mohamed (Frontiers in Bioengineering and Biotechnology, 2022)
Dodonaea oil was investigated as a possible source for biodiesel production in this study. Dodonaea (Dodonaea viscosa Jacq.) is an evergreen shrubby plant found in tropical and subtropical climates. The plant, which is naturally high in fats, produced high-quality biodiesel in both quantity and quality. Various ratios of oil to methanol, constant temperature (60o), reaction time (1hr), and different catalyst concentrations (0.25-0.75 percent W/w) were used in the transesterification followed by esterification reaction. The maximum biodiesel yield was achieved 90%. The prepared biodiesel was defined and compared to ASTM requirements for fuel properties analysis. Analytical techniques such as FT-IR and NMR spectroscopy were used to verify the chemical composition. In light of the above, Dodonaea is regarded as a potential bioenergy source; it will contribute better especially in the transportation field.